Procedimentos informatizados de ensino de sinais para adolescentes e adultos com surdez e/ou deficiência mental. - Elias, Nassim Chamel (Universidade Federal de São Carlos, 2007)
Language is essential to pass on complex concepts and allows the human being to communicate. In Behavior Analysis, the term verbal behavior has been used instead of language because it suggests its environmental determination. Stimulus equivalence paradigm treats verbal behavior as a complex behavior, installed through conditional discriminations, and has been largely used as a basis to investigate the process of complex cognitive skill acquisition and in practical applications to teach academic skills, such as reading, writing and mathematic, to individuals with and without developmental deficit. Conditional discriminations may be installed through matching-to-sample (MTS) tasks. In the present work Study 1, an automated tool was developed to present MTS tasks which were used in four experiments, in Study 2, to teach relations between signs (set A), pictures (set B) and printed words (set C) to teenagers and adults with deafness and mental retardation. The first experiment investigated whether, through the teaching of a receptive repertoire, the expressive repertoire would emerge without direct teaching to four adults with mental retardation and little or no experience in manual signing. The receptive repertoire refers to the selection of a picture in the presence of the corresponding sign (relations AB), in automated MTS tasks. The expressive repertoire refers to the expressive signing (A ) in the presence of a given picture (B). In the second experiment, a set of printed words was added and three adults with mental retardation and deafness and good signing experience were taught relations between printed words and pictures (CB) and between signs and pictures (AB); after teaching, the emergence of the relations between signs and printed words (AC) and of the expressive signing in the presence of the pictures (BA ) and printed words (CA ) were tested. The third experiment intended to replicate the second experiment with three teenagers with mental retardation and deafness and good signing experience, and also intended to investigate whether the repetition of the sign in MTS tasks would influence the acquisition of the taught relations (AB and AC) and the emergence of the tested relations (CB, BA and CA ). The fourth experiment investigated whether the introduction of consequences to the signing response in the presence of the pictures (BA ) would influence the signing performance in the presence of the printed words (CA ). In general, the emergence of the tested relations between signs, pictures and printed words and of expressive signing after the teaching in MTS tasks was observed. However, a better singing performance in the presence of the pictures (BA ) than in the presence of the printed words (CA ) was noted. Thus, future works could investigate the variables that would influence the acquisition of the signing repertoire in the presence of printed words, being this repertoire one of the reading components.
Keywords: Educação especial; Deficiência auditiva; Língua brasileira de sinais; Psicologia do comportamento; Equivalência de estímulo; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL